Situation Report: Romania, 28 June 1963 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reaction to President Kennedy's European Visit Tito on Romanian-Albanian Relations Romanian Cooperation in Comecon, Power Substation at Mucacevo [Mukacheve] Meetings of Machine-Building Experts News from Ethnic Schools